2012
DOI: 10.1038/nsmb.2416
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilins lock secreted semaphorins onto plexins in a ternary signaling complex

Abstract: Co-receptors add complexity to cell-cell signaling systems. The secreted semaphorin 3s (Sema3s) require a co-receptor, neuropilin (Nrp), to signal through plexin As (PlxnAs) in functions ranging from axon guidance to bone homeostasis, but the co-receptor’s role is obscure. Here we present the low resolution crystal structure of a mouse semaphorin-plexin-Nrp complex alongside unliganded component structures. Dimeric semaphorin, two copies of plexin and two copies of Nrp are arranged as a dimer of heterotrimers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
194
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(228 citation statements)
references
References 58 publications
13
194
2
1
Order By: Relevance
“…These results suggest again that when plexin-A2 is highly expressed it can transduce Sema3A and Sema3B signals independently of plexin-A4. These results are also in agreement with previous reports showing that at high plexin-A2 expression levels Sema3A can transduce signals through receptors containing complexes of NP1 and plexin-A2 (Janssen et al, 2012). Indeed, we found that Sema3A was able to induce the association of plexin-A2 with NP1 in cells overexpressing plexin-A2, whereas Sema3F was not able to promote such an association (Fig.…”
Section: Overexpression Of Plexin-a2 In Cells Silenced For Plexin-a1supporting
confidence: 83%
See 3 more Smart Citations
“…These results suggest again that when plexin-A2 is highly expressed it can transduce Sema3A and Sema3B signals independently of plexin-A4. These results are also in agreement with previous reports showing that at high plexin-A2 expression levels Sema3A can transduce signals through receptors containing complexes of NP1 and plexin-A2 (Janssen et al, 2012). Indeed, we found that Sema3A was able to induce the association of plexin-A2 with NP1 in cells overexpressing plexin-A2, whereas Sema3F was not able to promote such an association (Fig.…”
Section: Overexpression Of Plexin-a2 In Cells Silenced For Plexin-a1supporting
confidence: 83%
“…These observations suggest that the Sema3A signaling complex contains these three receptors, an assumption that is supported by coimmunoprecipitation experiments. Because plexin-A2 has also been reported to transduce Sema3A signals and to participate in the formation of functional Sema3A receptors (Takahashi and Strittmatter, 2001;Janssen et al, 2012), we sought to determine whether plexin-A2 also participates in the transduction of Sema3A signals in these cells. To examine this possibility, we inhibited the expression of plexin-A2 in HUVECs and in U87MG cells using two specific shRNA species that do not inhibit the expression of the other class A plexins or the expression of neuropilins ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Class 3 semaphorins (Sema3) transfer their function through a receptor complex consisting of plexins and neuropilin (NRP)-1 and -2 (140,141). Downstream signaling of Sema involves RhoA, RAC-1, and cofilin, leading to the reorganization of the cytoskeleton (142).…”
Section: Semaphorins and Their Receptorsmentioning
confidence: 99%